The Prevalence of Oral Protozoa Trichomona Stenax in some Patients with Gingivitis - Al-Khayat, Fadia A (Journal of Baghdad College of Dentistry, 2016)
Background:As arelationshipbetween gingivitis disease and the presence of the oral protozoa Trichomonastenax has been represented byconsiderable differences among various study population.The purpose of present study is determining the prevalence of T.tenax in patients with gingivitis and healthy subjects. Subjects,Materials and Methods:The presence of the parasite has been diagnosed with 58 patients withgingivitisand 58 healthy persons during the period of the study(April and May 2015) by taken two swabs for each one,microscopic examination was done using saline wet mount method and stained method. Age, sex and brushing teeth habit were in a count. Statistical analysis was done by SPSS program. Results:Gingivitis disease was observed in 58patients among the total 163 examined subjects(35.58%)with a highly significant differences P